The Linkage of Sulfonimidoyl Fluorides and Unactivated Alkenes via Hydrosulfonimidoylation - Zeng, Daming; Ma, Yinhao; Deng, Wei‐Ping; Wang, Ming; Jiang, Xuefeng (Angewandte Chemie International Edition, 2022)
Sulfur(VI) fluoride cleavage and exchanging linkage, a new generation of linkage chemistry, exhibits enormous potential for combining a range of functional molecules in an increasing number of fields. Herein, we established a metal‐free linkage of unactivated alkenes and sulfonimidoyl fluorides via hydrosulfonimidoylation to construct sulfoximines within minutes. An intermolecular hydride transfer process is the key step, and it occurs via overlap of the LUMO in the sulfonimidoyl cation and HOMO in the unactivated alkene, which was confirmed via control experiments with deuterated compounds. DFT calculations further demonstrated the concerted process involving formation of the S−C(sp3) bond and hydride transfer. Remarkably, abundant natural products and pharmaceuticals with multiple heteroatoms and sensitive functional groups have been subjected to the current linkage reaction to achieve various sulfoximine linkages, furnishing the basis for drug discovery and drug conjugation. A metal‐free linkage chemistry of unactivated alkenes and sulfonimidoyl fluorides via hydrosulfonimidoylation to construct sulfoximines within minutes is presented. An intermolecular hydride transfer process is the key step in the reaction.